Toward GPS Data Implementation for Structural Integrity Check of Offshore Platform - Widjajanti, Nurrohmat (2009)
The most generally offshore oil exploration-production platforms used the jacket-type fixed structures. In the reason of their long service in hostile environment, the platform require deformation monitoring for structural integrity. The integrity assessment is carried out to detect any deficiency of structural element strength, in point of view of structure’s safety and reliability. The assessment can be extended to identify and locate the possible structural defects for timely maintenance and repairs. Since the platforms are located hundred of kilometers from shore, Global Positioning System (GPS) technique give beneficial in enable to carry out deformation monitoring in term of geodetic approach. This is relevan to the task in maintaining regular surveillance over the stability of the offshore platform. The paper presents the preliminary study of offshore jacketed platform simulation for structural integrity check. GPS data displacement was applied as deformation restrain-input into the model of the platform structure. Four legs of the platforms were fixed at the sea bed while the restrains were loaded at the top side of the platform. Simulation result showed that structural integrity check utilizing GPS data displacement seems convincing to be further developed in the purpose of platform deformation monitoring.